Efektivitas Tetes Mata Citicoline terhadap Perbaikan Lapang Pandang dan Ketebalan Lapisan Serabut Saraf Retina pada Glaukoma Primer Sudut Terbuka - Metta Dewi; Ariel Valentino Soetedjo (Cermin Dunia Kedokteran, 2024)
Primary open-angle glaucoma (POAG) is the second leading cause of irreversible blindness worldwide with increasing prevalence. Oral citicoline has been shown to have a role in glaucoma; however, studies regarding citicoline eye drops for glaucoma are still limited. This is a critical appraisal of the literature on the effectiveness of citicoline in improving the mean deviation (MD) of the visual field and thickness of the retinal nerve fiber layer (RNFL) in POAG. A literature search was done on 4 databases: PubMed, Cochrane, Embase, and Scopus. From the 165 studies initially identified, 3 studies were qualified for critical review. Rossetti demonstrated significant MD (p=0.02) and RNFL (p=0.04) differences after 3 years of citicoline eye drops compared to placebo. Mirachtsis showed that after citicoline administration for 3 months there was a significant difference in RNFL (p=0.029), but no significant improvement in MD (p>0.05). Parisi showed an improvement in MD after 4 months (+0.56 dB) and 6 months (+0.18 dB) of citicoline administration. Citicoline eye drops have the potential to inhibit glaucoma progression by inhibiting RNFL loss, but further research is needed on visual field improvement.